Personal Pronouns Usage in Sir Arthur Conan Doyle's Sherlock Holmes Short Stories - Hilda Hastuti; Diah Supatmiwati; Lela Rahmawati; Nur Alfilail (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to identify and classify the use of personal pronouns in the collection of Sherlock Holmes short stories by Sir Arthur Conan Doyle based on the theory of Betty Schrampfer Azar. The study employed qualitative research. The data source consisted of six chapters of Sherlock Holmes short stories comprising 174 pages. The research showed there were 5,128 personal pronouns from chapter 1 to chapter 6 consisting of 2.815 with 54.89% subject pronouns, 976 with 19.03%, object pronouns, 28 with 0.55% possessive pronouns, 1.285 with 25.06% possessive adjective and 24 with 0.47% reflexive pronouns. The high frequency of subject pronouns indicates that the stories emphasize characters and narrators as the performers of actions. Therefore this study can be implied in grammar learning to improve English learner's comprehending of pronoun usage, cohesion, and coherence. It also contributes to literary texts in constructing characterization, narrative perspective, and meaning in a story.